Penerapan UML Dalam Sistem Reservasi Perawatan Puskesmas Cikampek Berbasis Website - Septiana, Aulia; Voutama, Apriade (INFORMAL: Informatics Journal, 2023)
As technology continues to advance, some Puskesmas are leveraging online services to seize opportunities. In order To keep pace with these developments, the Cikampek Health Center has mandated changes to implement web-based treatment bookings. Puskesmas are community facilities that function as health services. In this research, we designed an online reservation system consisting of use case diagrams, activity diagrams, sequence diagrams, class diagrams, and implementation using UML-based identification methods, analysis, and system design. The use of UML modeling is very effective and helps the reader understand the overall picture of the system being created. The results obtained in the construction of this system aim to make it easier for the community to access Puskesmas services, and the authors believe that this website will help reduce waiting times and improve the processing of patient data. I hope it will be a tool for promotion.